Diversity of Bacteria and the Characteristics of Actinobacteria Community Structure in Badain Jaran Desert and Tengger Desert of China - Sun, Ye; Shi, Yun-Lei; Wang, Hao; Zhang, Tao; Yu, Li-Yan; Sun, Henry; Zhang, Yu-Qin (Frontiers in Microbiology, 2018)
To assess the diversity of actinobacterial taxa in desert sands and obtain the novel microbial resources, 79 and 50 samples were collected from the Badain Jaran and Tengger Deserts of China, respectively. High-throughput sequencing of environmental 16S rRNA genes was conducted on an Illumina Miseq platform. Based on the HTS analyses, cultivation-dependent techniques were optimized to identify the cultivable Actinobacteria members. A total of 346,766 16S rRNA gene reads comprising 3,365 operational taxonomic units were obtained from the BJD sands, while 170,583 reads comprising 1,250 OTUs were detected in the TGD sands. Taxonomic classification indicated that Actinobacteria was the predominant phylum, comprising 35.0% and 29.4% of the communities in BJD and TGD, respectively. Among the Actinobacteria, the Geodermatophilaceae was considerably abundant in both deserts, indicating that they represent ubiquitous populations within the deserts, which may play a critical ecological role in deserts. At the genus level, Arthrobacter spp. and Kocuria spp. were dominant, and corresponded to 21.2% and 5.3% of the actinobacterial communities in BJD and TGD deserts, respectively. A total of 786 and 376 actinobacterial strains were isolated and identified from BJD and TGD samples, respectively. The isolates comprised 73 genera of 30 families within the phylum Actinobacteria. In addition to the Geodermatophilaceae, Streptomyces spp. were a prominent component of the isolates, comprising 25% of the isolates from BJD and 17.5% of those from TGD. Comparison of the actinobacterial community structure in other ecosystems indicated that Geodermatophilaceae were the main actinobacterial group in desert sands, which is consistent with our results. Additionally, in these desert habits, Geodermatophilaceae and some other core groups may promote or inhabit the subsequent members’ occurrence or prosper to shape the bacteria community structure. It should be noted that a number of other low-abundance bacteria appear to be specific to desert sands, which are worth further investigation. In antimicrobial activity assays, 10.36 % of the tested isolates showed antimicrobial activities in one or more screens. Importantly, 37 of the newly isolated strains representing novel taxa that could be valuable resources for further research of novel secondary metabolites and their ecological significance in deserts.